Rancangan Strategi Komunikasi Media Sosial Instagram @Wanadri_Coop dalam Membangun Citra Koperasi di Mata Generasi Z: Studi Kasus pada Koperasi Keluarga Besar Wanadri - Ami Purnamawati; Haikal Padli; Diyani Fauziyah (LPPM Universitas Koperasi Indonesia, 2026)
Both Z generation of cooperative members and nonmembers of KKB Wanadri slowly responded to the content of the @wanadri_coop Instagram account. The Unplanned as well as algorithm mismatch contents were not able to convey some information effectively. Although combining Instagram's collaboration features and promotion through WhatsApp and word of mouth, the results were still not optimal. The lack of communication strategies and human resources have become obstacles in forming a positive image of the cooperative. The research objectives were to find the description of the Instagram @wanadri_coop social media communication strategy in building the cooperative's image in view of Z Generation, identified efforts to create a positive image through social media, and design a social media communication strategy development model. The method used was a case study with the descriptive approach. The results of the study show that the SIRKEL-Z model can be used as a reference for the Instagram @wanadri_coop social media communication strategy, which consists of four main pillars: Share, Optimize, Manage, and Engage. Messages are conveyed through curated content and uploaded consistently to build a cooperative narrative that is relevant to Z Generation. Although the image of cooperatives among young people is still limited to savings and loans aspects and is considered unattractive, the Instagram account @wanadri_coop has shown a fairly positive image. Additionally, the Wanadri Cooperative also implements the Four Step Public Relations approach in building a positive image, namely problem identification, planning, communication implementation, and program evaluation, to enhance communication effectiveness and cooperative's appeal to especially the younger generation.